2012
DOI: 10.1158/1535-7163.mct-11-0963
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E2 Overexpression Is Associated with Endocrine Resistance but not Insensitivity to CDK2 Inhibition in Human Breast Cancer Cells

Abstract: Cyclin E2, but not cyclin E1, is included in several gene signatures that predict disease progression in either tamoxifen-resistant or metastatic breast cancer. We therefore examined the role of cyclin E2 in antiestrogen resistance in vitro and its potential for therapeutic targeting through cyclin-dependent kinase (CDK) inhibition. High expression of CCNE2, but not CCNE1, was characteristic of the luminal B and HER2 subtypes of breast cancer and was strongly predictive of shorter distant metastasis-free survi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(102 citation statements)
references
References 48 publications
(64 reference statements)
6
94
1
1
Order By: Relevance
“…Given the strong role for mitotic disregulation and genome instability in human cancer, we characterized the effects of cyclin E2 on these endpoints in estrogen receptor-positive breast cancer cells, a subtype that overexpresses cyclin E2 more strongly than cyclin E1. 22 Intriguingly, we found that while cyclin E2 overexpression did not affect mitotic progression, the protein still induced genomic instability via mechanisms that are distinct from cyclin E1-induced genomic instability. nuclear envelopes, as marked by the distinct membranous localization of Lamin A/C (Fig.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…Given the strong role for mitotic disregulation and genome instability in human cancer, we characterized the effects of cyclin E2 on these endpoints in estrogen receptor-positive breast cancer cells, a subtype that overexpresses cyclin E2 more strongly than cyclin E1. 22 Intriguingly, we found that while cyclin E2 overexpression did not affect mitotic progression, the protein still induced genomic instability via mechanisms that are distinct from cyclin E1-induced genomic instability. nuclear envelopes, as marked by the distinct membranous localization of Lamin A/C (Fig.…”
Section: Introductionmentioning
confidence: 68%
“…models. 1,32 However cyclin E2 mRNA is detected at high levels independently of cyclin E1 mRNA in various malignancies, 20,22 and cyclin E2 repeatedly features in signatures of poor prognosis in breast cancer that do not include cyclin E1. [33][34][35] We show here that cyclins E1 and E2 have distinct effects on progression through mitosis when overexpressed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical data indicated that although there were BC-ERP patients who were suitable for endocrine therapy, ~30% of BC-ERP patients exhibited resistance to endocrine drugs in the early stages of treatment (primary resistance), and ~40% BC-ERP of patients showed the effectiveness of endocrine therapy prior to exhibiting gradually reduced sensitivity or resistance with the extension of treatment time (7,8). This ERP status greatly affected the clinical efficacy, and even lead to the failure of clinical BC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Proper kinetics and expression level of cyclin E are crucial for its function during G1 to S phase transition, since its deregulated expression has been correlated with poor patient outcome in various human cancers including breast carcinoma (Keyomarsi and Pardee, 1993;Donnellan and Chetty, 1999;Caldon et al, 2012). In a retrospective studies, cyclin E level has been the best predictor of survival comparing with canonical clinical factors (age, tumor size, nodal status, stage of disease) and biologic markers (steroids and Her-2 receptor status, ploidy, proliferation index, cyclins D1 and D3) (Keyomarsi et al, 2002;Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%